A multi-criteria approach to the selection of the optimal investment alternative with software support - Zoran Nešić; Dragana Radojičić; Radomir Šalić (Anali Ekonomskog fakulteta u Subotici, 2020)
In this paper, some possibilities of implementing information technology in investment management are presented. The paper deals with the choice of the optimal investment alternative out of a series of alternatives compared, evaluated in the system of different and heterogeneous criteria with different requirements for the extremization with different relative significance. The analysis of the criteria was performed from the aspect of production capacities, investment value, the required number of employees, the internal rate of return, investment maintenance, as well as the logistical and technological levels. The choice of the optimal alternative was made by the multicriteria decision-making methods with developed software support for this purpose. The results indicate the agreement of the optimal alternative, i.e. the rank of the compared alternatives, through the parallel application of the two multicriteria decision methods. In the paper, the compromise programming method and a modified approach to the Promethee multicriteria decision-making method that allows the analysis of an unlimited number of different preferential functions are applied. The application of certain preferential functions is analyzed from the point of view of individual criteria applied in this paper. The paper presents the general options for choosing investment alternatives from several most significant aspects, with an analysis of the preferences of the individual criteria. The application of the presented methodology enables a sophisticated approach to criteria analysis. On the other hand, the software solution developed for this purpose enables simplicity and applicability in practical conditions of use.